Políticas de saúde mental para efetivação de um cuidado integral na atenção básica - Silva Filho, Luciano Belas e (2018)
In the context of the Sanitary Reform that resulted in the Unified Health System, the society also began to reflect on the Psychiatric Reform, which deals with the care provided to people with mental disorders and on the understanding of the relative issues to crazy and madness, in the search for a model of care that would guarantee the integrality of the actions, their universal access and ensure the protection of human rights. The Psychiatric Reform movement proposes transformations of practices, knowledge, cultural and social values, arguing that only in this way will it be possible to overcome the traditional psychiatric model. The proposals of the reform guide the care directed towards the subject in his suffering, for his territory and his community, considering the historical context and the health needs. Therefore, the Basic Attention, although it is configured as strategic for objectifying the assumptions of Psychiatric Reform, currently still has the challenge of aligning mental health care with general health. In this sense, the present study aims to investigate the contents of the Mental Health Policy - theory and practice - that characterize Mental Health care in Primary Care, aiming to subsidize the elaboration of a decision model for the evaluation of Health Districts from the municipality of João Pessoa. From this perspective, two methodological approaches were adopted: qualitative and quantitative. The qualitative approach was carried out to identify the qualifying themes and the consequent alignment to the categories taken a priori, which are the two health models existing in society today: the Traditional Health Model and the Expanded Health Model. Subsequently, weights were assigned for each variable of the instrument used in the quantitative approach research. The latter was developed with professionals from 80 family health units that, in responding to the instrument on mental health actions, in Primary Care allowed the evaluation and characterization of the health units of the family of health districts in: Linked to the Model Traditional, Next to the Traditional Model, In Transition, Next to the Expanded Model and Linked to the Expanded Model. The decision model used in the study was based on the Classical Theory of Tests (CTT), which allowed the verification that the "In Transition" and "Next to the Expanded Model" decisions were the most frequent for all districts. In this sense, it was possible to highlight the potential of the decision model developed, in the present study, as an evaluation tool, in the context of Basic Attention. The information obtained through the decision model is useful for a better understanding of the work process of the teams and for making better decisions for the problem cut out.